2020
DOI: 10.1158/1078-0432.ccr-20-2483
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of SRC Kinase Activity Augments PARP Inhibitor–mediated Synthetic Lethality in BRCA2-altered Prostate Tumors

Abstract: Purpose: Alterations in DNA damage repair (DDR) pathway genes occur in 20-25% of men with metastatic castration-resistant prostate cancer (mCRPC). Although poly (adenosine diphosphate [ADP]-ribose) polymerase inhibitors (PARPi) have been shown to benefit men with mCRPC harboring DDR defects due to mutations in BRCA1/2 and ATM, additional treatments are necessary because the effects are not durable. Experimental Design:We performed transcriptomic analysis of publicly available mCRPC cases, comparing BRCA2-null … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…In another study, Chakraborty et al (2021) designed a specific sgRNA to target expression of BRCA2, a key component of DNA damage repair (DDR). Its mutations have a tight association with prostate cancer oncological events [ 196 ]. Variations in DDR pathway genes such as BRCA1 / 2 and ATM occur in 20–25% of men with metastatic castration-resistant prostate cancer (mCRPC) and complicate cancer cell resistance to therapeutic modalities [ 196 ].…”
Section: Crispr/cas9 In Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Chakraborty et al (2021) designed a specific sgRNA to target expression of BRCA2, a key component of DNA damage repair (DDR). Its mutations have a tight association with prostate cancer oncological events [ 196 ]. Variations in DDR pathway genes such as BRCA1 / 2 and ATM occur in 20–25% of men with metastatic castration-resistant prostate cancer (mCRPC) and complicate cancer cell resistance to therapeutic modalities [ 196 ].…”
Section: Crispr/cas9 In Cancersmentioning
confidence: 99%
“…Variations in DDR pathway genes such as BRCA1 / 2 and ATM occur in 20–25% of men with metastatic castration-resistant prostate cancer (mCRPC) and complicate cancer cell resistance to therapeutic modalities [ 196 ]. They found that genetic depletion of BRCA2 established by the CRISPR system caused an antiproliferative effect on prostate cancer cells and enhanced their susceptibility to poly (ADP-ribose) polymerase (PARP) inhibitors, FDA-approved drugs for mCRPC treatment [ 196 ]. Finally, double KO of Akt1 and Akt2 genes potently decreased prostate cancer cell metastasis in vitro and in vivo [ 197 ].…”
Section: Crispr/cas9 In Cancersmentioning
confidence: 99%
“…Milk-derived aflatoxins may thus modify aldo-keto reductase activities, which are in the focus of recent PCa research [552][553][554] . Furthermore, it has been demonstrated in lung cancer cell lines that AFB1 upregulates insulin receptor substrate 2; induces SRC, AKT, and ERK1/2 phosphorylation; and stimulates cancer cell migration, which was inhibited by saracatinib [555] , a kinase inhibitor under investigation in the treatment of PCa [556][557][558][559] . Thus, milk-derived aflatoxins may amplify SRC-and AKT-mediated prostate carcinogenesis.…”
Section: Aflatoxinsmentioning
confidence: 99%
“… 32 , 33 In a previous study, the combined use of Src inhibitors (DAS) and PARP inhibitors (OLA) increased the sensitivity of prostate cancer to OLA, and the inhibition of Src signaling by DAS increased DNA damage in prostate cancer cells, showing favorable therapeutic effects. 34 Moreover, in another study, DAS inhibited cell cycle detection point kinase 1 (Chk1) and induced DNA damage, while OLA inhibited damaged DNA repair. 35 Therefore, the combination of DAS and OLA appears to be a promising treatment for triple negative breast cancer.…”
Section: Introductionmentioning
confidence: 98%